Pengaruh Pembiasaan Berbusana Muslimah terhadap Peningkatam Akhlak Mulia Peserta Didik Kelas XI di MAN 2 Bogor - Nurfitriani, Dea; Supriadi, Dedi; Siti, Noneng (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The background to the problem of this research is that students do not meet the criteria for Muslim women's clothing, such as covering the entire body/genitals which must be covered. This is proven by the fact that there are still students whose clothing does not comply with school regulations. Where students still wear tight clothes and wear very narrow skirts, they assume that Muslim dress is only a school rule. Therefore, to solve the problem above, one solution is to use the habit of wearing Muslim clothing. The aim of the research was to determine the habit of wearing Muslim women's clothing in class The research method uses field research with a quantitative approach and data collection uses observation and questionnaires. The results of the research show that the simple linear regression test value is known to be Tcount = 4.178 > Ttable 1.686, so it can be concluded that the variable habituation to Muslim women's clothing (X) influences the variable noble morals (Y).